STARLING PENJUAL KOPI PASURUAN GO SYARIAH: POTRET TENTANG QRIS BSI MENEMBUS EKOSISTEM JALANAN - Saiful Anam, Muhammad; Haryanti, Peni (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
This study discusses the phenomenon of Starling, or mobile coffee vendors in Pasuruan, who have begun to utilise BSI Go Syariah QRIS as a medium for daily transactions. This phenomenon not only demonstrates a change in the economic behaviour of street micro-businesses, but also illustrates the effectiveness of BSI's marketing in penetrating the informal economic segment. This study aims to explore how the use of BSI QRIS by Starling vendors can support ease of transaction, enhance customer experience, and strengthen BSI's position as a provider of sharia financial services that is adaptive to grassroots market needs. The research method uses a descriptive qualitative approach through field observations and in-depth interviews with Starling vendors and customers in the Pasuruan area. The results show that BSI's QRIS facilitates cashless transactions, reduces the risks associated with cash, and helps merchants record their daily income more regularly. From a marketing perspective, the adoption of BSI's QRIS in the street ecosystem is evidence of the success of BSI's market penetration strategy, particularly because customers feel more comfortable conducting sharia-compliant transactions. However, challenges remain in the form of digital literacy and internet connectivity issues. Overall, BSI's QRIS has proven effective in expanding BSI's marketing reach and strengthening its presence in the street economy.